Local Variation in Ground Arthropod Diversity Rises as Distance to Residential Areas Decreases in a Mature Evergreen Forest - Jing Su; Meili Wang; Hui Liu; Wenqi Shang; Fanfang Zhou; Haochen Cao; Jinwen Pan; Yang Zeng; Kun Xu; Ganghua Li (Diversity)
Ground-dwelling arthropods interact with vertebrates, plants, detritus, and microbes as important players in forest ecosystems. Human disturbance threatens the diversity of forest arthropods, with varied impacts on different taxa. However, we understand little of the impact of human disturbance on overwintering ground-dwelling arthropod diversity in mature subtropical evergreen forests. In order to test how ground-dwelling arthropod diversity varies by the distance to residential areas, we set 108 pitfall traps along four 100 m transects beginning near residential areas along the edges of a mature subtropical evergreen forest in Central China. We collected 30,616 arthropods, representing 96 morphospecies. The results show that the Shannon, Simpson, and Pielou’s evenness indices, as well as the effective number of species at α = 1 and 2, decrease when the pitfall traps are within 60 m of the residential areas. Moreover, the coefficients of variation in these three indices are higher at the sites closer to the residential areas by 11.54–17.72%. Such high variations in these widely used diversity and evenness indices indicate that estimation bias in arthropod diversity is more likely to occur at sites closer to residential areas. We suggest that different aspects of community composition should be studied to assess the effects of human disturbance on ground-dwelling arthropod diversity.